2023
DOI: 10.1177/14604582231164697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of using WeChat/WhatsApp on physical and psychosocial health outcomes among oncology patients: A systematic review

Abstract: The purpose of this systematic review is to summarize the potential effects of the WeChat and WhatsApp mobile applications in cancer management. This systematic review was written in accordance with PRISMA guidelines. CINAHL, PubMed, ProQuest Nursing and Allied Health Database, PsycINFO, PsycARTICLES, and ERIC were utilized for the literature search. Articles were included if they evaluated the outcomes of using WeChat/WhatsApp for cancer management, and excluded if they were qualitative studies, not published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Work outcomes always have a difference between one and the other. It is according with the previous research statement was mentioned that WhatsApp considered the most popular messaging services application around the world, it is more than 100 countries where over the 2.5 billion is the active user of WhatsApp [18]. Therefore, health professional including manager in Timor-Leste is very need to understanding and able to adapt in the digital WhatsApp use to facilitate their fast communication, and also need to help those who do not have access to these technologies to improve their future services.…”
Section: Digital Technology Utilization Experiencesmentioning
confidence: 68%
“…Work outcomes always have a difference between one and the other. It is according with the previous research statement was mentioned that WhatsApp considered the most popular messaging services application around the world, it is more than 100 countries where over the 2.5 billion is the active user of WhatsApp [18]. Therefore, health professional including manager in Timor-Leste is very need to understanding and able to adapt in the digital WhatsApp use to facilitate their fast communication, and also need to help those who do not have access to these technologies to improve their future services.…”
Section: Digital Technology Utilization Experiencesmentioning
confidence: 68%
“…Many studies have reported using WeChat to manage chronic diseases such as hypertension, diabetes, coronary heart disease, and cancer. 28,[36][37][38][39][40][41] WeChat has also positively impacted medical students 42 and patients with schizophrenia. 43 Herein, 73.3% of patients considered it necessary to establish a WeChat group for PD patients, and 65.7% believed that the significance of establishing a WeChat can provide Relatively comfortable relationship.…”
Section: Health Knowledge Needs Of Pd Patientsmentioning
confidence: 99%
“…While outcomes related to sleep and rehospitalization rates also improved, they did not reach statistical significance. However, findings related to anxiety, fatigue, and adverse drug reactions were inconsistent among the included studies [6].…”
mentioning
confidence: 98%